THE ROLE OF ARTIFICIAL INTELLIGENCE IN DECISION-MAKING AND INNOVATION IN PRODUCT DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW - GLUŠČEVIĆ, Luka; IVANIŠEVIĆ, Rajko (Journal of process management and new technologies, 2025)
Artificial intelligence is changing how organizations develop products and make decisions. This literature review shows that AI is now a key driver for innovation and efficiency in product management. Companies use AI tools to improve every stage of the product lifecycle, from idea creation to final delivery and ongoing updates. AI helps managers analyze large sets of data, predict market trends, and speed up decision processes. Instead of replacing people, AI often supports human work by allowing teams to solve complex problems and test new ideas faster. However, successful AI adoption depends on quality data, organizational readiness, and clear strategies. Main challenges include technical questions, data trust, ethical issues, and staff training. Best practices highlight the importance of combining human expertise with AI tools, using agile methods, and developing transparent, responsible systems. Research gaps remain in understanding AI’s long-term effects, especially in non-digital sectors and on employee motivation. This review provides a structured overview of trends, challenges, and future research directions for AI in product management and decision-making.